IMPORTANCE OF EXTERNAL AND INTERNAL ENVIRONMENT IN CREATION OF COMPETITIVE ADVANTAGE TO SMEs. (CASE OF SMEs, IN THE NORTHERN REGION OF ALBANIA) - Ylvije Borici Kraja; Elez Osmani (European Scientific Journal, ESJ, 2015)
External and internal factors have crucial impact to SMEs environment. Nowadays business environment is more global and competitive than it has been in the past. A broad range of business factors are connected to SME’ competitive advantage. The aim of this research is to show the importance of external and internal factors in creation of the SME’s competitive advantage. The resource – based view of the SMEs, such as capabilities, competencies etc., and the threat of new entrants, rivalry, threat of substitutes, supplier power and buying power; the combine of these factors are in the center of this study. Firms need to better understand the competitive environment and develop strategies that create sustained competitive advantage. Then we present our study methodology used on this study which consists in a combination of qualitative and quantitative method. To realize the aim of this study are determines some objectives and research question pertaining the impact of the external and internal factors, such as Porter’s five forces or, tangible and intagible assets in the creation of competitive advantage etc. Based on the research questions are made hypothesis. The empirical analyze is done to understand the potential sources of competitive advantage for SMEs. Study consists on a final sample of 460 participant from different small and medium enterprises in Northern Albanian Region. It is used regression analysis. The result revealed that both, external and internal factors have positive affect in competitive advantages of SMEs. Based on the result of this analyze are done conclusions. Findings support the idea, within limitations, that external environment have greater impact than internal environment on SME’s success. Results strongly suggest some important academic and practitioner implications and some suitable recommendations.